Targeting TRP Channels For Novel Migraine Therapeutics - Dussor, Gregory (ACS Chem Neurosci, 2014)
[Image: see text] Migraine is increasingly understood to be a disorder of the brain. In susceptible individuals, a variety of “triggers” may influence altered central excitability, resulting in the activation and sensitization of trigeminal nociceptive afferents surrounding blood vessels (i.e., the trigeminovascular system), leading to migraine pain. Transient receptor potential (TRP) channels are expressed in a subset of dural afferents, including those containing calcitonin gene related peptide (CGRP). Activation of TRP channels promotes excitation of nociceptive afferent fibers and potentially lead to pain. In addition to pain, allodynia to mechanical and cold stimuli can result from sensitization of both peripheral afferents and of central pain pathways. TRP channels respond to a variety of endogenous conditions including chemical mediators and low pH. These channels can be activated by exogenous stimuli including a wide range of chemical and environmental irritants, some of which have been demonstrated to trigger migraine in humans. Activation of TRP channels can elicit CGRP release, and blocking the effects of CGRP through receptor antagonism or antibody strategies has been demonstrated to be effective in the treatment of migraine. Identification of approaches that can prevent activation of TRP channels provides an additional novel strategy for discovery of migraine therapeutics.